Phage morphology recapitulates phylogeny: the comparative genomics of a new group of myoviruses. - André M Comeau (Public Library of Science (PLoS), 2012)
Among dsDNA tailed bacteriophages (Caudovirales), members of the Myoviridae family have the most sophisticated virion design that includes a complex contractile tail structure. The Myoviridae generally have larger genomes than the other phage families. Relatively few "dwarf" myoviruses, those with a genome size of less than 50 kb such as those of the Mu group, have been analyzed in extenso. Here we report on the genome sequencing and morphological characterization of a new group of such phages that infect a diverse range of Proteobacteria, namely Aeromonas salmonicida phage 56, Vibrio cholerae phages 138 and CP-T1, Bdellovibrio phage φ1422, and Pectobacterium carotovorum phage ZF40. This group of dwarf myoviruses shares an identical virion morphology, characterized by usually short contractile tails, and have genome sizes of approximately 45 kb. Although their genome sequences are variable in their lysogeny, replication, and host adaption modules, presumably reflecting differing lifestyles and hosts, their structural and morphogenesis modules have been evolutionarily constrained by their virion morphology. Comparative genomic analysis reveals that these phages, along with related prophage genomes, form a new coherent group within the Myoviridae. The results presented in this communication support the hypothesis that the diversity of phages may be more structured than generally believed and that the innumerable phages in the biosphere all belong to discrete lineages or families.